THE ROLE OF GAME TECHNIQUES IN TEACHING SPEECH CULTURE IN THE PHILOLOGICAL FIELD - Mamatkulova Nilufar Boyzak kizi (International Journal of Pedagogics, 2024)
This article explores the role of game techniques in the process of teaching speech culture in the philological field. It highlights the relevance of using game approaches in educational practice in order to effectively develop students' communication skills. The author analyzes the basic principles and methods of game learning, revealing their applicability and effectiveness in the context of the formation of speech culture. The pedagogical aspects of the introduction of game techniques into the educational process of philological specialties, including the selection and adaptation of game tasks, evaluation and monitoring of results, are also considered. The results of the study emphasize the importance of game techniques as a means of stimulating active communication, increasing students' motivation to study speech culture and developing their skills of language adaptation and etiquette. Possible obstacles and ways to overcome them when introducing game approaches into the educational process are also analyzed. In general, the article represents an important contribution to the pedagogical practice of teaching speech culture in the philological field, justifying the need and prospects for using game techniques to achieve educational goals.